2021
DOI: 10.3390/molecules26144109
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization, Antiproliferative and Antioxidant Activities of Polyunsaturated Fatty Acid-Rich Extracts from Chlorella sp. S14

Abstract: Microalgae is a rich source of polyunsaturated fatty acid. This study was conducted to identify and isolate microalgal strain with the potentials for producing polyunsaturated fatty acids (PUFAs) and determine its cytotoxic effect on some cancer cells. The algal strain (Chlorella sp. S14) was cultivated using modified BG-11 media, and algal biomass obtained was used for fatty acid extraction. Gas chromatographic–mass spectrometry was used to identify and quantify the levels of the fatty acid constituents. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Fatty acid profiling results suggested that both Ano and Rho diatom FAs showed potential for use as bioactive ingredients for dietary supplements with high nutritional qualities. intensity and nutrients [13]. This should be examined in further studies.…”
Section: Characterization Of Diatom Lipidsmentioning
confidence: 90%
See 3 more Smart Citations
“…Fatty acid profiling results suggested that both Ano and Rho diatom FAs showed potential for use as bioactive ingredients for dietary supplements with high nutritional qualities. intensity and nutrients [13]. This should be examined in further studies.…”
Section: Characterization Of Diatom Lipidsmentioning
confidence: 90%
“…Variations in findings were attributable to the different growing conditions of microalgae [6], while additional molecules other than lipids from the solvent employed in the extraction process contributed to the total weight of lipid [23]. intensity and nutrients [13]. This should be examined in further studies.…”
Section: Characterization Of Diatom Lipidsmentioning
confidence: 95%
See 2 more Smart Citations
“…In recent years, research on medicinal plants as potential chemotherapeutic agents has increased globally because of their actions that prevent cancer initiation and proliferation with limited toxicity, as well as their anti-multidrug reversal ability [86,87]. There are very few scientific studies on Merremia species as anticancer agents, but their traditional use in treating breast cancer may have prompted investigations on their potential anticancer and antiproliferative properties as discussed below.…”
Section: Cancer Cell Cytotoxicitymentioning
confidence: 99%